(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
This case study focuses on identifying a deceased person by establishing paternity and sibship relationships with alleged relatives through unique sharing of alleles. Bone and blood samples from the deceased were provided, along with reference blood samples from an alleged son and an alleged brother. DNA extracted from these samples was quantified, amplified, and analysed using an 8-capillary array DNA analyzer. By an extremely rare coincidence, each amplified autosomal locus in the DNA profiles from both the alleged son and the alleged brother shared at least one allele with the corresponding locus in the DNA profiles from the tissue samples of the deceased. The alleged relationships were further investigated through Y-STR analysis, which confirmed their same immediate patrilineal relationship. To establish the degree of paternity and sibling relationships, we calculated the respective indices and confirmed the relationship to the deceased individual. This is the first case we have encountered where both the son and the brother share autosomal DNA fragments at all amplified loci in the absence of the mother’s reference sample. This forensic study highlights the importance of DNA statistics in determining the strength of relationships based solely on STR results, allowing conclusions to be drawn without further testing as per the alleged relationships.